Needle stick injuries in nurses at a tertiary health care facility - Khushdil, Arshad; Farrukh, Huma; Sabir, Moin ud Din; Awan, Tayyaba; Qureshi, Tayyaba (Journal of Postgraduate Medical Institute, 2013)
Objective: This study was aimed to assess the frequency and factors associated with Needle Stick Injuries(NSI) in nurses of a tertiary health care facility. Methodology: This cross-sectional descriptive study was conducted in Combined Military Hospital Lahorein June-July 2012. Responses were obtained via a self-administered questionnaire with close-ended questionsabout the knowledge of the nurses regarding hazards of NSI, their frequency, and methods theypractice to prevent them. The data was analyzed using SPSS-16. Chi-square test was applied and p-valuewas fixed at 0.05 to be statistically significant. Results: Out of 118 nurses who participated, all were aware of the occupational hazards of their professionwhen they joined nursing. Sixty Five (55%) got NSI and 38(58%) of those were injured at the timeof recapping the syringe. Sixty Nine (58.5%) did not use gloves while administering injections. After gettingstuck by a contaminated needle, 100% squeezed out the blood from the area and 45(69%) out of 65 nursescleaned the wound with a spirit swab. Only 13(20%) out of 65 consulted a physician regarding safetymeasures after NSI and 35(53%) had screening for Hepatitis-B Virus (HBV). Seventy Eight (66%) of thetotal 118 nurses were immunized against HBV. Conclusion: Needle-stick injuries are highly prevalent among nurses, and prevention is the most effectiveway to protect nurses from infectious diseases which these injuries can transmit. Mandatory reporting tothe concerned authorities, proper follow up, screening of nurses after NSI and promotion of safety measuresagainst it should be greatly encouraged.